Moral Corruption and Virtue in Posidonius’s Thought. A Re-Examination of Some Fragments - Zago, Giovanni (ΠΗΓΗ/FONS, 2020)
This article offers a text-critical and exegetical re-examination of some fragments of Posidonius on moral corruption and virtue (Sen. Ep . 90, 6 = Posidon. F 284 EK = F 448 Th; D.L. VII 91 = Posidon. F 29 EK = F 403 Th; D.L. VII 91 = Posidon. F 2 EK = 435b Th), as well as of other related texts (Verg. Aen . VIII 313-328; Strab. XVI 2, 35-39 = Posidon. F 133 Th; Sen. Ep . 89, 8). The author sheds new light on Posidonius’s conception of the golden age (which can be reconstructed starting from Seneca’s epistle 90) and on the text of Strab. XVI 2, 35-39; proposes a new interpretation of Posidon. F 29 EK and an emendation to Posidon. F 2 EK; notices for the first time the Posidonian background of Sen. Ep . 89, 8.
Keywords: Posidonius; fragments; textual criticism; moral corruption; virtue